Polish Emigrants on Organizational Culture of Austrian Companies - Chmielewska-Muciek Dorota (Management, 2018)
The paper is of theoretical and empirical character. It outlines considerations and studies pertaining to the perception of organizational culture of Austrian companies by Polish emigrants. When undertaking employment abroad, emigrants face a challenge of adapting to a new environment. The adaptation pertains to several aspects. Organizational culture is one of these. Therefore, the following research problem arises: What is the organizational culture of Austrian enterprises like?, and, Do emigrants experience problems with the cultural adaptation? Interviews with 40 Poles who worked a minimum of 5 years in Austria were conducted. The interviews revealed that respondents believed the organizational culture of Austrian companies was characterized by low power distance, individualism, activity, and status based upon achievements. The straightforward analysis was difficult to be made with regard to several values. This is true for low vs. high uncertainty tolerance, people vs. task focus, and focus on the outside vs. inside. The identified organizational culture of Austrian enterprises did not pose a significant barrier for respondents.